Distribusi Spasial Kualitas Perairan Pantai Pasir Mayang Kabupaten Kayong Utara Provinsi Kalimantan Barat - Saputra, Robin; Zibar, Zan; Raynaldo, Adityo; Shofiyah, Sofi Siti; Marista, Etha; Sugara, Ayub (Jurnal Laot Ilmu Kelautan, 2023)
Monitoring the quality and condition of waters is an importantactivity to carry out, especially in coastal waters which are veryeasily contaminated and prone to pollution. The waters of PasirMayang Beach are influenced by inputs from rivers and theactivities of coastal communities, which in turn affect the waterquality and aquatic organisms. The purpose of this study was todetermine the condition of water quality using seawater qualitystandards and map them spatially. Water quality parameterssurveyed included temperature, salinity, pH, oxygen level andbrightness which were measured at 17 survey locations. Thesurvey method used was direct data measurement and the datawas grouped into tabular form using Ms. Excel 2010 and theresults were compared and matched with seawater qualitystandards stipulated by the Minister of Environment RegulationNo. 51 of 2004. Spatial distribution was carried out using ArcGIS10.4 software and interpolated using the inverse distanceweighting (IDW) method. Measurement and analysis results wereobtained for temperature parameters between 30-31.6 °C.Salinity 11.3 to 21.7 ‰. pH 7.0-7.9;DO 2.1-3.6mg/L. Based onthe research results, the following conclusions can be drawn:Some of the seawater quality of Pasir Mayang Beach still meetsthe established quality standards, including temperature and pH,so that it can be further classified according to its function.However, there are several parameters that do not meet qualitystandards, namely: Salinity, DO and Clarity. For theeDOparameter, thereeareeseverallresearchhstationssthat are stillwithin or below the quality standard.